2002
DOI: 10.1136/jme.28.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to physician and family assisted suicide: results from a study of public attitudes in Britain

Abstract: L egalisation of assisted suicide presents a dilemma for society. This arises because of a lack of consensus regarding the precedence to be accorded freedom of choice versus the inviolability of human life. A combination of factors has served to throw this dilemma into sharper focus in recent times. These include population aging, 1 2 increased openness regarding end-of-life care, 3 development of patients' rights, and increasing secularisation and multiculturalism in society. Against this backdrop and within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 9 publications
2
26
0
2
Order By: Relevance
“…A UK-based survey found over half of the general population favoured legalising PAS (O'Neill et al, 2002), but the questions asked of the public in both these studies involved a 'painful' physical illness rather than a deterioration of mind. Previous studies in the United States have shown differences in attitudes to PAS and life-sustaining treatments among different ethnic groups (Lichenstein et al, 1997;Gessert et al, 2001;Owen et al, 2001;Butt et al, 2003;Phipps et al, 2003) but we are unaware of similar research in the UK.…”
Section: Introductionmentioning
confidence: 98%
“…A UK-based survey found over half of the general population favoured legalising PAS (O'Neill et al, 2002), but the questions asked of the public in both these studies involved a 'painful' physical illness rather than a deterioration of mind. Previous studies in the United States have shown differences in attitudes to PAS and life-sustaining treatments among different ethnic groups (Lichenstein et al, 1997;Gessert et al, 2001;Owen et al, 2001;Butt et al, 2003;Phipps et al, 2003) but we are unaware of similar research in the UK.…”
Section: Introductionmentioning
confidence: 98%
“…71 Finally, the use of religious or spiritual beliefs as a source of support and comfort was associated with less suicidal ideation among 835 African-American senior residents of public housings, after controlling for social and medical variables. 72 The level of religiousness also has been found to be inversely associated with the acceptance of euthanasia and physician-assisted suicide in the general population in Britain, 73 among the elderly in the US, physicians in Australia 75 and cancer patients in a palliative care service in the US. 76 Non-religious Belgian general practitioners were three times more frequently involved than the religious physicians in deaths resulting from administration of (lethal) drugs with the explicit intention of hastening the end of life of the patient without his/her explicit request.…”
mentioning
confidence: 99%
“…British Social Attitude (BSA) Surveys conducted between 1983-1994(O'Neill, Feenan, Hughes, & McAlister, 2003 show high levels of the UK public supporting assisted dying, with 75-84% of those questioned supporting the legalisation of physician-assisted suicide, for example. A recent BSA survey (Clery, McLean, & Phillips, 2007) indicates higher support in cases where a person has a terminal illness.…”
Section: Opinion Poll Evidencementioning
confidence: 99%